2021
DOI: 10.1088/1361-6560/ac212c
|View full text |Cite
|
Sign up to set email alerts
|

Investigating beam range uncertainty in proton prostate treatment using pelvic-like biological phantoms

Abstract: This study aims to develop a method for verifying site-specific and/or beam path specific proton beam range, which could reduce range uncertainty margins and the associated treatment complications. It investigates the range uncertainties from both CT HU to relative stopping power conversion and patient positioning errors for prostate treatment using pelvic-like biological phantoms. Three 25 × 14 × 12 cm3 phantoms, made of fresh animal tissues mimicking the pelvic anatomies of prostate patients, were scanned wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The range uncertainty with prostate treatment is estimated at approximately 3% of the path length. 49 With the reduced path length afforded by anterior oblique beams, the net range uncertainty is diminished, resulting in improved treatment robustness. We found that CTV coverage robustness with a +3 mm y axis shift was improved with use of 4 fields.…”
Section: Discussionmentioning
confidence: 99%
“…The range uncertainty with prostate treatment is estimated at approximately 3% of the path length. 49 With the reduced path length afforded by anterior oblique beams, the net range uncertainty is diminished, resulting in improved treatment robustness. We found that CTV coverage robustness with a +3 mm y axis shift was improved with use of 4 fields.…”
Section: Discussionmentioning
confidence: 99%
“…Range errors can affect the distal end of the beam, causing an underdose/overdose on the edge of the target, which creates a mismatch between the film and TPS [ 21 23 ]. Issues arise with the introduction of air bubbles resultant from filling the phantom with water before simulation and again before treatment.…”
Section: Discussionmentioning
confidence: 99%